Substance use confounds associations between peer victimization and aggression in adolescence with mental disorders in adulthood: A prospective birth cohort study. Issue 7 (26th July 2022) - Sarala, Marian; Miettunen, Jouko; Alakokkare, Anni‐Emilia; Mustonen, Antti; Scott, James G.; Thomas, Hannah J.; Hurtig, Tuula; Niemelä, Solja
Abstract: Introduction: Peer victimization and aggression in adolescence are associated with later mental health morbidity. However, studies examining this association have not controlled for adolescent substance use. We aimed to study the associations between peer victimization, peer aggression, and mental disorders in adulthood, adjusting for substance use in adolescence. Methods: Participants were from the prospective Northern Finland Birth Cohort 1986. Data were available for 6682 individuals (70.8% of the original sample). Peer victimization and peer aggression were assessed with items from the Achenbach Youth Self Report at ages 15−16 years. Outcomes were nonorganic psychosis, anxiety disorder, mood disorder, substance use disorder, and any mental disorder (a none‐vs‐any indicator) at age 33 years collected from nationwide health care, insurance, and pension registers. Family structure, alcohol intoxication frequency, daily smoking, illicit drug use, and baseline psychopathology using Youth Self‐Report total score, and parental mental disorders were considered as confounding factors. Results: In multivariable analyses, the association between peer victimization and psychosis (Hazard ratio [HR]: 2.9, 95% confidence interval [CI]: 1.2−6.9, p  = .020) and mood disorder (HR: 1.7, 95% CI: 1.2−2.4, p  = .012) in females remained significant after adjusting for confounders. Other associations between female and male peer victimization or aggression and the studied outcomes attenuated after adjustments. Conclusions: Some associations between peer victimization and aggression and later mental health morbidity are explained by adolescent substance use. For females, substance use does not account for the increased risk of psychosis and mood disorder in those who experience peer victimization.